Entrepreneurship, institutional framework and support mechanisms in the EU - Apostolopoulos, Nikolaos; Chalvatzis, Konstantinos; Liargovas, Panagiotis (Emerald Publishing Limited, 2021)
Over recent decades a variety of tools, regulations, and funding and support schemes have been developed in the EU to promote and enhance entrepreneurial activities. However, research supporting entrepreneurial activities in the EU remains under-researched. Entrepreneurship, Institutional Framework and Support Mechanisms in the EU aims to shed some light on the important and yet crucially under-explored interactions between entrepreneurship, institutions and support mechanisms within the EU. This collective volume sets the foundations of a comprehensive discussion which focuses on the determinants of boosting EU entrepreneurship in local, regional, national and supranational levels. With its scope will extend to all major, relevant and interrelated aspects, Entrepreneurship, Institutional Framework and Support Mechanisms in the EU provides a go-to source of current thinking in this area.